A Laboratory Based Investigation of a New Elastic Toothbrush Head - Lorenzo Mazza; Maria Rosaria Gatto; Giuseppe Monaco; Gian Andrea Pelliccioni (The Scientific World Journal)
Purpose. To demonstrate the noninferiority of a new toothbrush head with retractile bristles compared to traditional toothbrush heads on dental models. Methods. The new toothbrush head, mounted on manual and electrical handles, presents retractile bristle groups that can singularly retract over its entire length and offer calibrated resistance. Fourteen gypsum models of dental arches, twelve with and two without anatomical impairments, were spread with a “plaque simulator.” Each arch was brushed twice with each of the four toothbrushes, one minute by the same operator, blinded to the study. The plaque index (PI) was recorded at the end of each brushing session. GLM for repeated measures analysed the data. Results. On all the casts, the manual prototype and the electric prototype, removed 11% and 14% more “plaque simulator” compared to the standard toothbrush. In presence of dental anomalies, the prototypes removed 13% and 16% more plaque, respectively, compared to standard toothbrushes (P=0.04). In both situations, the 95% confidence intervals of PI did not include −10% (the minimal margin of clinical relevance). Conclusions. The prototype is more effective in removing plaque from the casts with anomalies. The noninferiority of the prototype with respect to the standard toothbrushes was demonstrated.